Evaluación de silages a partir de pescado procesados con ácido cítrico y cloruro de sodio - Sánchez Valarezo, Haidyn Gerardo (2011)
The present work was realized in the laboratory of Technology and Processing of Aquatic Organisms of the Faculty of Agropecuary Sciences of Machala's University, province of El Oro, where which aims were: 1. To evaluate the effect of the Citric Acid and of the Chloride of Sodium in the processing of the silage; 2. To determine the multifaceted level in the elaborated ensilados; 3. To determine the range of the extract of subtle necessary lemon to transform the raw material sweet little face (Selene peruviana) in silage. In the present investigation a species of little was in use commercial value as source of protein, the same one that chemist was submitted to the traditional procedure of production of silage, but changing the strong acids, for extract of subtle lemon and stabilizing the growth of fungi with chloride of sodium, for which realized 5 treatments (75ml/100gr; 100ml/100gr; 125ml/100gr; 150ml/100gr; 175mlExtrac lemon /100grClNa) in 454gr of fish, with 5 repetitions, obtaining a total 25 samples, which were evaluated by means of: Analysis Organoleptic, Feasibility study and Evidence dietetics, us allowing to expire hereby with our raised aims.